2017
DOI: 10.3233/cbm-170362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prostate cancer hub genes and therapeutic agents using bioinformatics approach

Abstract: The BMP2, PPARG and PRKAR2B genes may therefore be potential biomarkers in the treatment of PCa. Additionally, the small molecular agent phenoxybenzamine may be a potential drug for PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…As marked in bold fonts in Table 6, there were some overlapped findings between our studies and other studies: our identified hub genes FOXA1, CDH1, and EPCAM were seen in 2 (Endo et al 2009; Tan et al 2019), 1 (Fang et al 2017), and 1 (Lu 2019) other studies, respectively. Next, we further validated our findings using data from TCGA.…”
Section: Validation Of Hub Genes Expression In Multiple Databasessupporting
confidence: 50%
See 2 more Smart Citations
“…As marked in bold fonts in Table 6, there were some overlapped findings between our studies and other studies: our identified hub genes FOXA1, CDH1, and EPCAM were seen in 2 (Endo et al 2009; Tan et al 2019), 1 (Fang et al 2017), and 1 (Lu 2019) other studies, respectively. Next, we further validated our findings using data from TCGA.…”
Section: Validation Of Hub Genes Expression In Multiple Databasessupporting
confidence: 50%
“…As shown in Table 6, the literature search in Pubmed/GEO regarding gene expression profiles of PCa versus NP tissues yielded 10 relevant studies, 5 (Chen et al 2012;Endo et al 2009;Fan et al 2018;Fang et al 2017;He et al 2018) of which were based on a single GEO dataset whereas the other 5 studies (Lu 2019;Song et al 2019b;Tan et al 2019;Tong et al 2019;Zhao et al 2017) were integrated bioinformatic analyses based on multiple GEO datasets. The hub genes reported by the 10 eligible studies were extracted and compared with those identified in the present study.…”
Section: Validation Of Hub Genes Expression In Multiple Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicated that CD81 functions as an oncogene in prostate cancer and may be a potential prognostic biomarker for human prostate cancer. In recent years, an increasing number of studies have focused on the development of accurate molecular biomarkers for better detection, diagnosis, prognosis, and treatment (18)(19)(20). For instance, forkhead transcription factor (FoxM1) functions as an oncogene in the initiation, development, and progression of cancer, and its neoplastic functions can be used as a strong biomarker for the diagnosis and treatment of cancer (21).…”
Section: Discussionmentioning
confidence: 99%
“…Many comparative analyses of the DEGs have been carried out on cancers in recent years. [7][8][9] However, none of the aforementioned studies has been completely investigated in AL amyloidosis.…”
Section: Introductionmentioning
confidence: 99%